Linking oxysterols and different stages of mild cognitive impairment: insights from gut metabolites and N6-methyladenosine - Wenjing Feng; Mengwei Ju; Tao Wang; Shanshan Cui; Kexin Yang; Zhiting Guo; Miao Liu; Jiaxuan Tao; Huiyan Yu; Rong Xiao (Alzheimer’s Research & Therapy)
Abstract Background Oxysterols, gut metabolites, and N6-methyladenosine (m6A) are extensively implicated in the pathogenesis of cognitive dysfunction, while their alterations in different stages of mild cognitive impairment (MCI) have not been elucidated. Therefore, this study was conducted to explore the associations of oxysterols, gut metabolites, and m6A methylation profiles in early MCI (EMCI) and late MCI (LMCI) individuals. Methods Liquid chromatography-mass spectrometry, untargeted metabolomic analysis, and m6A mRNA Epitranscriptomic Microarray were used to detect the characteristics of serum oxysterols (n = 35/group), fecal gut metabolites (n = 30/group), and m6A in whole blood (n = 4/group) respectively. The concentration of serum β-amyloid (Aβ) was detected with ELISA (n = 25/group). The gene expression of amyloid precursor protein (APP) and its key enzyme β-secretase (BACE1) in whole blood were measured by quantitative real-time PCR (n = 25/group). Results EMCIs and LMCIs, especially LMCIs, exhibited poorer performance in almost all global and multidimensional cognitive tests. Serum 27-hydroxycholesterol (27-OHC) and 24S-hydroxycholesterol (24S-OHC) were elevated in EMCI and LMCI groups. Changes in gut metabolites occurred mainly in the EMCI group, in which several gut metabolites, including Procyanidin dimer B7 and Phorbol myristate, were significantly decreased. The m6A methylation landscape of EMCIs and LMCIs obviously differed from Controls. Hypomethylated mRNAs accounted for the majority and were mainly accompanied by downregulated mRNAs, which was consistent with the downregulated expression of the m6A writer methyltransferase-like 4 (METTL4). 27-OHC and 24S-OHC combined with various gut metabolites significantly distinguished between MCI subgroups from healthy controls (EMCI/Control: AUC = 0.877; LMCI/Control: AUC = 0.952). Heatmap revealed the correlation between Phorbol myristate and differentially m6A-methylated mRNAs. Differentially expressed gut metabolites and methylated mRNAs were commonly enriched in 34 KEGG metabolic pathways, including cholesterol metabolism and neurodegenerative disease-related pathways. Conclusions Our study explored the altered oxysterols, gut metabolites, and m6A methylation and their associations in different stages of MCI. The potential function of aberrant gut metabolites in oxysterols and m6A methylation driving MCI progression warrants further mechanistic investigation.